2002
DOI: 10.1161/01.cir.0000031161.77536.02
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload Augments Angiotensin II–Induced Cardiac Fibrosis and Promotes Neointima Formation

Abstract: Background-Abnormal iron deposition may cause oxidant-induced damage in various organs. We have previously reported that continuous administration of angiotensin II to rats results in an overt iron deposition in the renal tubular epithelial cells, which may have a role in angiotensin II-induced renal damage. In the present study, we investigated the role of iron in the development of cardiac injury induced by angiotensin II. Methods and Results-Angiotensin II was continuously infused to rats at a dose of 0.7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…Interestingly, however, Yokohama et al (34) have very recently reported that AT1 receptor antagonism not only suppressed the hepatic fibrosis, but also reduced the serum ferritin content. In addition, we have demonstrated that ANG II administration to rats caused deposition of iron and induction of ferritin in the heart and that AT1 receptor blockade decreased the extent of fibrosis and expression of ferritin in the heart (16). Together with the current results, it is suggested that ANG II may act to promote organ fibrosis, in part, via modulating iron homeostasis, and this can be suppressed by the AT1 receptor antagonism.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, however, Yokohama et al (34) have very recently reported that AT1 receptor antagonism not only suppressed the hepatic fibrosis, but also reduced the serum ferritin content. In addition, we have demonstrated that ANG II administration to rats caused deposition of iron and induction of ferritin in the heart and that AT1 receptor blockade decreased the extent of fibrosis and expression of ferritin in the heart (16). Together with the current results, it is suggested that ANG II may act to promote organ fibrosis, in part, via modulating iron homeostasis, and this can be suppressed by the AT1 receptor antagonism.…”
Section: Discussionsupporting
confidence: 74%
“…We recently demonstrated that ANG II infusion into rats causes iron deposition and the induction of ferritin expression in the kidney (14) and heart (16), which may augment the profibrotic effects of this peptide. Iron catalyzes Fenton and Haber-Weiss reactions to generate toxic hydroxyl radicals and the consequent products of lipid peroxidation.…”
mentioning
confidence: 99%
“…14 Although the interaction between angiotensin II and hepatic iron overload has not been well defined, animal experiments have recently shown that chronic administration of angiotensin II induces iron deposition in the heart, leading to cardiac fibrosis, and that this effect is blocked by losartan administration. 8 As in the heart, angiotensin II may provoke hepatic iron deposition, and losartan may inhibit this action. Angiotensin II has been reported to enhance insulin resistance, and this effect was reversed by angiotensin II receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated a crucial role of angiotensin II in the pathogenesis of hepatic fibrosis, 6 and this peptide has been shown to enhance insulin resistance and tissue iron deposition. 7,8 Administration of an antagonist of angiotensin II type 1 receptor has been shown to decrease hepatic fibrosis in rats. 6 In the present study, the effects of losartan, a selective angiotensin II type I receptor antagonist, were investigated in patients with NASH.…”
Section: N Onalcoholic Steatohepatitis (Nash) Is a Dis-mentioning
confidence: 99%
“…In previous studies, we have reported that long-term administration of angiotensin II (Ang II) in rats caused accumulation of iron in the kidney, 13,14 heart, 15 and liver, 16 and that this may play a role in regulating the gene expression and function in these organs. Thus far, little is known about whether Ang II induces aberrant iron homeostasis in the vascular tissue; however, if so, it might exacerbate the oxidant-induced vascular damage initiated by increased production of superoxide 17 generated by activated NAD(P)H oxidase.…”
Section: See Page 2235mentioning
confidence: 99%